At kalde sygdommen ved dens rette navn. Om spedalskhed i Sydindien - Aagard-Hansen, Jens (Tidsskriftet Antropologi, 2019)
The article focuses on communication in a medical anthropological context. Based on empirical data from a leprosy eradication programme in Tamil Nadu in India, it is indicated how the terminology and the semantics of the sickness influence the medical work. During the fieldwork, 3 biomedical synonyms and 24 Tamil layterms were registered. The choice of label for the ailment in question had clear implications for health education activities, population surveys, as well as treatment compliance.